2017
DOI: 10.4330/wjc.v9.i7.620
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis and thoracic aortic disease: A review on forgotten psychological aspects

Abstract: AIMTo summarize the current evidence on psychological issues in thoracic aortic disease (TAD) and infective endocarditis (IE) setting.METHODSWe performed a narrative review about psychological issues in adults with IE and TAD. Through the electronic databases, PubMed and PsycINFO, we searched full manuscripts in English and published until September 1, 2014.RESULTSWe found sixteen studies exploring psychological issues in patients with IE (six studies) and in TAD (ten papers). Psychological issues assessed wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Endocarditis-related mortality has remained steadily high since 2000 and is strongly associated with several risk factors, such as advanced age, a high Charlson comorbidity index, non-community acquisition, prosthetic valves, staphylococcal infections, perivalvular complications, stroke, and the non-performance of surgery when indicated ( 3 , 4 , 11 , 16 , 31 , 32 ). Of note, studies on psychological outcomes in survivors after an episode of endocarditis have demonstrated a reduction in quality of life and the occurrence of posttraumatic stress disorder ( 33 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…Endocarditis-related mortality has remained steadily high since 2000 and is strongly associated with several risk factors, such as advanced age, a high Charlson comorbidity index, non-community acquisition, prosthetic valves, staphylococcal infections, perivalvular complications, stroke, and the non-performance of surgery when indicated ( 3 , 4 , 11 , 16 , 31 , 32 ). Of note, studies on psychological outcomes in survivors after an episode of endocarditis have demonstrated a reduction in quality of life and the occurrence of posttraumatic stress disorder ( 33 ).…”
Section: Epidemiologymentioning
confidence: 99%
“…A study noted that the U.S. spent approximately twice as much as other high income countries on healthcare (19) . The initial median admission duration from our data lasted approximately 9 days, while median readmission number was 10 days (IQR, [5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Essentially, we are spending more .…”
Section: Discussionmentioning
confidence: 98%
“…The copyright holder for this preprint this version posted June 5, 2021. ; https://doi.org/10.1101/2021.06.04.21258024 doi: medRxiv preprint work and activities of daily living (17) . There was also another study that reported to find that 1 in 4 patients had self-reported symptoms of anxiety and depression (18) .…”
Section: Discussionmentioning
confidence: 99%
“…The article, “Infective endocarditis and thoracic aortic disease: a review on forgotten psychological issues” by Marianna Bagnasco provides a very good overview of the studies related to the psychological and quality of life outcomes related to infective endocarditis and thoracic aortic disease[ 1 ]. However there are a few points that could be addressed when interpreting this dataset.…”
Section: Commentary On Hot Topicsmentioning
confidence: 99%